Investigation of titanium mesh as a cathode for the electro-Fenton process: consideration of its practical application in wastewater treatment. Issue 6 (17th April 2020) - Lee, Jiho; Son, Aseom; Ko, Young-Jin; Shin, Min-Jung; Kim, Woong Sub; Choi, Jae Woo; Lee, Jaesang; Hong, Seok Won
Abstract : We show that a Ti electrode with a large opening size is a promising cathode material in the application of the electro-Fenton process for degradation of organic pollutants in wastewater treatment. Abstract : This study investigated the performance of organic pollutant degradation using the electro-Fenton process and low-cost titanium (Ti) electrodes as cathodes. Three Ti electrodes with different morphologies, i.e., a plate and two meshes with large (MS-L) and small (MS-S) opening sizes, were evaluated using electrochemical characterization, as well as kinetic and energy studies based on the COD removal performance of the electro-Fenton process. The preliminary results indicated that the MS-S electrode, which has the largest electrochemically active surface area and lowest resistance amongst the three electrodes, could reduce Fe 3+ to Fe 2+ most effectively in the synthetic solution. However, when treating real wastewater, MS-L rather than MS-S exhibited 13.8% higher COD removal efficiency with a 1.5-fold higher rate constant ( i.e., 0.0362 min −1 ) during the initial 30 min of the electro-Fenton process. This unexpected anomaly was due to excessive clogging by suspended solids (SS) present in the real wastewater that were easily captured by the narrow openings of MS-S. Consequently, a pilot-scale electro-Fenton system was operated using MS-L. The pilot experiment demonstrated stable degradation of organic pollutants for five consecutive months with an average COD removal efficiency of 86%, showing its feasibility in treating real wastewater. With its competitive regeneration of Fe 2+, low manufacturing cost and energy consumption, the electro-Fenton process using Ti mesh with large opening sizes appears to be a viable and practical technology for wastewater treatment.